Healthy Living: Taking Care from Head to Toe - Jennifer Hillan (EDIS)
FCS8821, a 2-page fact sheet by Jennifer Hillan, reminds patients with diabetes about the special precautions they need to take to protect their skin, eyes, teeth, gums, and feet and gives tips for keeping these parts of the body healthy. Published by the UF Department of Family, Youth and Community Sciences, December 2006.